Henry VIII - Travis, Peter (Quezon City : Magnavision.)
In the five centuries since his death, the life and legacy of Henry VIII (Ray Winstone, Sexy Beast), one of England's most infamous monarchs who reigned over the violent and sexually charged political minefield of Tudor Court, has continued to fascinate life few other historical figures, form charismatic prince to dissolute and depressed king, we follow the life and loves of Henry in a world where the politics of the bedroom were as lethal as those on the battlefield. This is the extraordinary saga of Henry VIII. The king who dismantled the church when it would not grant him the divorce he wanted; the husband who married six wives - women by turn humbled, bewitching, pious, victimized, adulterous, and devoted; the man who ruthlessly dispensed his daughter and - above all - longed for a son.